A Bufferable Tuned-Mass Damper of an Offshore Platform against Stroke and Response Delay Problems under Earthquake Loads. (29th November 2016) - Wu, Qiong; Zhao, Xilu; He, Shuai; Tang, Wenxian; Zheng, Rencheng
Abstract : A tuned-mass damper (TMD) is applied to ensure the safety and stability of an offshore platform in practice; however, damper stroke and response delay problems always result in intractable performances of vibration control while exposed to large earthquake loads. Therefore, this paper proposes a bufferable TMD, a passive TMD with buffers on both sides, to improve the performance of offshore platforms subjected to large seismic waves. A comprehensive simulation and experimental study was executed to investigate the dynamic performances of the bufferable TMD, by application of a 1 : 200-scale offshore platform prototype. It is verified that the bufferable TMD can be effective in absorbing the stroke energy, while the damper exceeds limitations of motion. Meanwhile, the bufferable TMD can maintain high-response characteristics. In conclusion, the experimental results indicate that the displacement, acceleration, and frequency performances of an offshore platform can be significantly decreased, and the evaluation indices show that the method is effective in reducing overall vibration levels and maximum peak values, with the application of the bufferable damper system.